The Prevalence and Predictors of Herbal Medicines’ Use in Cancer: A systematic Review and Meta-analysis of Observational Studies. - Asiimwe, John, Baptist; Ahmed, Sarki; Kamatenesi, Mauda, Mugisha; Atukunda, Esther, Cathyln; Prakash, PN; Ogwang, Patrick; Tolo, Casimu, Umba (My University, 2020)
The study aims to estimate the prevalence of herbal medicines use in cancer patients across the various regions of the world (geographical regions, economic regions) and establish the key predictors of herbal medicines use in those regions. The study will only synthesize literature from primary observational studies (cohorts and crosssectional study) reported in english between 2000 and 2020 (current). This study is evisaged to provide updated data on the magnitude of herbal medicine in cancer, that will in the end guide healthcare policy.
Keywords: Herbal medicines; Cancer; Meta-analysis